Purification of phenolic compounds from genipap (Genipa americana L.) extract by the ultrasound assisted ultrafiltration process - Madrona, Grasiele Scaramal; Terra, Natália Mazzarioli; Coutinho Filho, Ubirajara; Magalhães, Flávia de Santana; Cardoso, Vicelma Luiz; Reis, Miria Hespanhol Miranda (Acta Scientiarum. Technology, 2019)
Â The aim of this study was to evaluate the potential of an integrated membrane process for purification of polyphenol and genipin components from genipap fruit extract. Optimal conditions for aqueous extraction of polyphenols from genipap fruit pulp were at 71Â°C for 49 min using a fruit pulp:water ratio of 1:3 (w w-1). Microfiltration with membranes of different pore sizes (0.22, 0.3 and 0.8 Âµm) resulted in a clarified permeate with similar physical-chemical properties, but the permeate flux through the 0.8 Âµm membrane was higher than through the other membranes. The sequential ultrafiltration process reduced even more total and soluble solids of the microfiltered extract. Purities of polyphenols and genipin were, respectively, 2.5 and 1.2 times greater in the permeate than in the feed stream. Application of ultrasound during the ultrafiltration increased the steady state permeate flux and the purities of polyphenols and genipin in the permeate stream. Results suggest application of microfiltration as a clarification step followed by the ultrasound assisted ultrafiltration to produce a purified genipap extract with high contents of polyphenols and genipin. Â